Crop traits drive soil carbon sequestration under organic farming. Issue 5 (15th February 2018) - García‐Palacios, Pablo; Gattinger, Andreas; Bracht‐Jørgensen, Helene; Brussaard, Lijbert; Carvalho, Filipe; Castro, Helena; Clément, Jean‐Christophe; De Deyn, Gerlinde; D'Hertefeldt, Tina; Foulquier, Arnaud; Hedlund, Katarina; Lavorel, Sandra; et al.
Abstract: Organic farming (OF) enhances top soil organic carbon (SOC) stocks in croplands compared with conventional farming (CF), which can contribute to sequester C. As farming system differences in the amount of C inputs to soil (e.g. fertilization and crop residues) are not enough to explain such increase, shifts in crop residue traits important for soil C losses such as litter decomposition may also play a role. To assess whether crop residue (leaf and root) traits determined SOC sequestration responses to OF, we coupled a global meta‐analysis with field measurements across a European‐wide network of sites. In the meta‐analysis, we related crop species averages of leaf N, leaf‐dry matter content, fine‐root C and N, with SOC stocks and sequestration responses in OF vs. CF. Across six European sites, we measured the management‐induced changes in SOC stocks and leaf litter traits after long‐term ecological intensive (e.g. OF) vs. CF comparisons. Our global meta‐analysis showed that the positive OF‐effects on soil respiration, SOC stocks, and SOC sequestration rates were significant even in organic farms with low manure application rates. Although fertilization intensity was the main driver of OF‐effects on SOC, leaf and root N concentrations also played a significant role. Across the six European sites, changes towards higher leaf litter N in CF also promoted lower SOC stocks. Our results highlight that crop species displaying traits indicative of resource‐acquisitive strategies (e.g. high leaf and root N) increase the difference in SOC between OF and CF. Indeed, changes towards higher crop residue decomposability was related with decreased SOC stocks under CF across European sites. Synthesis and applications . Our study emphasizes that, with management, changes in crop residue traits contribute to the positive effects of organic farming (OF) on soil carbon sequestration. These results provide a clear message to land managers: the choice of crop species, and more importantly their functional traits (e.g. leave and root nitrogen), should be considered in addition to management practices and climate, when evaluating the potential of OF for climate change mitigation. Abstract : Our study emphasizes that, with management, changes in crop residue traits contribute to the positive effects of organic farming (OF) on soil carbon sequestration. These results provide a clear message to land managers: the choice of crop species, and more importantly their functional traits (e.g. leave and root nitrogen), should be considered in addition to management practices and climate, when evaluating the potential of OF for climate change mitigation.